(untitled) (Forseti. Law Review, 2026)
Before the contract is signed, disputes are handled in administrative proceedings before a tribunal, whose decisions may be challenged through judicial review. Sanctions imposed for conduct related to public procurement are also subject to judicial review. In this article, I analyze the particular features of the administrative judicial process in which these decisions are reviewed.